2019
DOI: 10.1038/s41467-018-07996-z
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of rapid electron precipitation via chorus element wave–particle interactions

Abstract: Chorus waves, among the most intense electromagnetic emissions in the Earth’s magnetosphere, magnetized planets, and laboratory plasmas, play an important role in the acceleration and loss of energetic electrons in the plasma universe through resonant interactions with electrons. However, the spatial evolution of the electron resonant interactions with electromagnetic waves remains poorly understood owing to imaging difficulties. Here we provide a compelling visualization of chorus element wave–particle intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 55 publications
6
55
0
Order By: Relevance
“…Moreover, chorus waves are one of the most important loss mechanisms of plasma sheet electrons via pitch angle scattering (e.g., Horne et al, ). The scattered electrons into the upper atmosphere could then generate microbursts (e.g., Breneman et al, ; Nakamura et al, ; Shumko et al, ), pulsating aurora (e.g., W. Li et al, ; Nishimura et al, ; Nishimura, Bortnik, Li, Thorne, Lyons, et al, ; Nishimura, Bortnik, Li, Thorne, Chen, et al, ; Ozaki et al, , ), and diffuse aurora (e.g., Ni et al, ; Thorne et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, chorus waves are one of the most important loss mechanisms of plasma sheet electrons via pitch angle scattering (e.g., Horne et al, ). The scattered electrons into the upper atmosphere could then generate microbursts (e.g., Breneman et al, ; Nakamura et al, ; Shumko et al, ), pulsating aurora (e.g., W. Li et al, ; Nishimura et al, ; Nishimura, Bortnik, Li, Thorne, Lyons, et al, ; Nishimura, Bortnik, Li, Thorne, Chen, et al, ; Ozaki et al, , ), and diffuse aurora (e.g., Ni et al, ; Thorne et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…At a higher L shell, that is, L ~ 11, Agapitov et al () showed a case with a larger scale size of chorus element, around 3,000 km, using Time History of Events and Macroscale Interactions during Substorms (THEMIS) observations. Moreover, the scale size of chorus waves is estimated by mapping the size of microburst and pulsating aurora onto the equatorial plane (e.g., Breneman et al, ; Nishimura, Bortnik, Li, Thorne, Lyons, et al, ; Nishimura, Bortnik, Li, Thorne, Chen, et al, ; Ozaki et al, , ; Shumko et al, ). On the nightside at L ~ 8, the latitudinal (longitudinal) size of pulsating aurora is found to be a few tens (hundreds) kilometers, which is roughly 3,000–7,000 km when mapping onto the equatorial plane (Nishimura, Bortnik, Li, Thorne, Chen, et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most statistical studies rely primarily on time-averaged spectral data, which obscures the true amplitude of short-lived, large-amplitude wave packets. Ozaki et al (2019) observed that large (hundreds of picoteslas), isolated chorus wave packets directly caused auroral flashes seen from ground stations. These large-amplitude whistler mode waves interact differently with electrons than their lower-amplitude counterparts, resulting in trapping, and rapid energization or de-energization, and pitch angle scattering (Bortnik et al, 2008;Cattell et al, 2008;Kellogg et al, 2010;Kersten et al, 2011;Omura et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Chorus emissions are generated near the equatorial plane in the magnetosphere by high-energy electrons with temperature anisotropy (e.g., Kennel & Petschek, 1966;LeDocq et al, 1998;Santolik et al, 2003). Chorus emissions are known to accelerate electrons to relativistic energy levels in the outer radiation belt and scatter them at the electron pitch angle through wave-particle interactions (e.g., Horne et al, 2007;Kasahara et al, 2018;Li et al, 2014;Meredith et al, 2003;Miyoshi et al, 2015;Ozaki et al, 2019). QP emissions are categorized as discrete electromagnetic waves with QP intensity enhancement on a time scale of ∼10-400 s (e.g., Manninen et al, 2014Manninen et al, , 2018Nemec et al, 2016;Titova et al, 2015).…”
Section: Introductionmentioning
confidence: 99%